Market Pricing of Banks’ Fair Value Assets Reported under Sfas 157 During the 2008 Economic Crisis - GOH, Beng Wee (Institutional Knowledge at Singapore Management University, 2009)
Our paper presents early evidence on how investors rely on the fair value estimates of assets reported by banks as required by Statement of Financial Accounting Standards No. 157 (SFAS 157) in 2008. We observe significant variation in the pricing of different levels of fair value assets, with the pricing being less for mark-to-model assets (i.e., assets with lower liquidity and greater information risk) than for mark-to-market assets. We also find that the pricing of mark-to-model assets declined over the course of 2008, consistent with increasing market concerns about illiquidity and information risk associated with these assets. In the cross-section, we find evidence that mark-to-model assets are priced higher by investors for banks with greater capital adequacy. We also find that the pricing of fair value assets, especially the mark-to-model assets, is higher when banks are audited by better auditors. Overall, our paper uses both time-series and cross-sectional analyses to provide insights on investors' valuation of the fair value estimates of assets as reported by banks during the economic crisis.